'Stepping back and moving in': the role of the state in the contemporary food regime. Issue 3 (3rd May 2016) - Pritchard, Bill; Dixon, Jane; Hull, Elizabeth; Choithani, Chetan
Abstract : In recent years, a number of middle-income countries and influential multilateral institutions have instigated actions that frame food system governance around social protection and rights. These state-centered mobilizations raise fundamental questions about how to portray the global politics of food. Since the late 1980s, analysts have largely concurred that US hegemony in the global politics of food has given way to diverse and volatile neo-liberalist and corporate-led food system governance. However, what should we make of a situation where state and supra-state actors are flexing their powers to reshape food systems in line with rights-based models? Should this be understood as reflexes which aim to preserve national order, at a time of intensified food and nutrition insecurities? Or, does it lay the foundations of a re-governed system which curbs and molds a corporate-led politics of food within frameworks of justice? This contribution responds to these questions by tracing the evolution of social protection and rights-based approaches to the politics of food at the multilateral level and in two influential jurisdictions (India and South Africa). We argue that these initiatives underline a robust and continuing role of state power in global food politics, albeit in a novel fashion compared to previous entanglements.